EXPLORATION OF BEAUVERIA BASSIANA ENTOMOPATHOGEN ON LEPTOCORISA ACUTA IN RICEFIELD - Mohammad Yunus; Salmirna Salmirna; Nur Edy (AGROLAND The Agricultural Sciences Journal (e-Journal), 2022)
Beauveria bassiana (Bals.) Vuill is a fungus that infecting the insect Leptocorisa oratorius F. naturally in ricefields. This study aimed to obtain isolates of the entomopathogenic fungus B. bassiana from the insects body of infected L. oratorius, which would later be used as biological agents in controlling rice pests. The exploratory research was carried out at rice production centers in Sidera Village, Sigi Regency and in Dolago Village, Parigi-Moutong Regency, Central Sulawesi. The laboratory tests were carried out at the Plant Disease Laboratory, Faculty of Agriculture, Tadulako University. Research methods include exploring L. oratorius insects infected by B. bassiana in the field, and then the specimens were brought to the laboratory for isolation and identification, calculation of conidia density, colony relative growth rate, and determination of viability. The results showed that L. oratorius was infected with the fungus B. bassiana in Sidera and in Dolago. Isolates from both regions had the same macroscopic and microscopic morphological characteristics, but had different characteristics of conidia density, colony relative growth rate, and viability.